High-Resolution Genomic Analysis of Cribriform Neuroepithelial Tumors of the Central Nervous System. Issue 10 (October 2015) - Gessi, Marco; Japp, Anna Sophia; Dreschmann, Verena; zur Mühlen, Anja; Goschzik, Tobias; Dörner, Evelyn; Pietsch, Torsten
Abstract : Abstract: Cribriform neuroepithelial tumors (CRINET) are one of several recently characterized entities in the broad spectrum of solid tumors with SMARCB1-INI1 loss. This neoplasm seems to be exceedingly rare and displays unique neuropathologic and clinical features. To date, only a few cases of CRINET have been characterized from a molecular point of view. In this study, we investigated the molecular features of 3 cases of CRINET using multiplex ligation-dependent probe amplification and molecular inversion profiling approaches. Along with mutations and deletions of SMARCB1-INI1, molecular inversion profiling analysis revealed a stable genomic profile without significant large chromosomal changes. Focal alterations (gains) were observed in individual cases at chromosomes 4q12 ( PDGFRA ), 12q15 ( MDM2 ), 7p15.1 ( NPY ), and 18q11.2 ( CDH2 ). Genomic Identification of Significant Targets in Cancer analysis highlighted focal alterations, including gains at chromosomes 16q23.2 ( MAF ), 17q23 ( AXIN2 ), and 8p12 ( ADAM3A ). No cases showed BRAF V600E or CTNNB1 mutations. These data indicate that CRINET present stable genetic features and lack alterations commonly identified in other pediatric brain tumors. Further studies are required to determine whether specific alterations and specific signaling pathways, in addition to SMARCB1-INI1, may be implicated in the biology of this rare tumor and whether there are additional molecular similarities between CRINET and atypical teratoid/rhabdoid tumors.